# trig

posted by .

simplify the expression.

cot^2(x)-csc^2(-x)

• trig -

csc(-x) = -csc(x)

sin^2+cos^2 = 1

• trig -

But my teacher gave the answer on the review as -1.

• trig -

but but but ... you should have used my hints.

csc^2(-x) = (-cscx)^2 = csc^2(x)

sin^2+cos^2 = 1
divide by sin^2 to get
1+cot^2 = csc^2
cot^2 - csc^2 = -1

sin^2+cos^2=1 will help solve many problems.

## Similar Questions

1. ### Math - Trig

I'm trying to verify these trigonometric identities. 1. 1 / [sec(x) * tan(x)] = csc(x) - sin(x) 2. csc(x) - sin(x) = cos(x) * cot(x) 3. 1/tan(x) + 1/cot(x) = tan(x) + cot(x) 4. csc(-x)/sec(-x) = -cot(x)
2. ### trig 30

For csc^2 A-1/cot A csc A, what is the simplest equivalent trig expression?
3. ### trig

prove the identity: csc x-1/csc x+1 = cot^x/csc^x+2 csc x+1
4. ### trig

For each expression in column I, choose the expression from column II to complete an identity: Column I Column II 1. -tanxcosx A. sin^2x/cos^2x 2. sec^2x-1 B. 1/sec^2x 3. sec x/cscx C. sin(-x) 4. 1+sin^2x D.csc^2x-cot^2x+sin^2x 5. …
5. ### math

use the quotient and reciprocal identities to simplify the given expression cot t sin t csc t sin t tan t cot t cot t sec t
6. ### trig

use basic identities to simplify the expression. csc θ cot θ / sec θ
7. ### trig

simplify the expression. (sin^2x+cos^2x) - (csc^2x-cot^2x)
8. ### trig

simplify the expression. cos^2x+sin^2x/cot^2x-csc^2x
9. ### Trig verifying identities

I am having trouble with this problem. sec^2(pi/2-x)-1= cot ^2x I got : By cofunction identity sec(90 degrees - x) = csc x secx csc-1 = cot^2x Then split sec x and csc-1 into two fractions and multiplied both numerator and denominators …
10. ### trig

verify (csc^4-1)/cot^2x=2+cot^2x So this is what I have so far on the left side (csc^2x+1)(cscx+1)(cscx-1)/cot^2x =(csc^2x+1)(cot^2x)/cot^2x i think I'm doing something wrong. Please help!

More Similar Questions

Post a New Question